Case Report: Idiopathic hypereosinophilic syndrome presenting with gastrointestinal involvement mimicking IBD: a diagnostic challenge - Amer, Johnny; Noori, Fathalla; Hamdan, Dareen; Mokhaimar, Turkey; Salhab, Ahmad (Frontiers in Medicine, 2025)
BackgroundIdiopathic hypereosinophilic syndrome (iHES) is a rare hematologic condition characterized by persistent, unexplained eosinophilia and organ involvement. Its diagnosis is challenging due to overlapping features with other eosinophilic and inflammatory gastrointestinal disorders.Case presentationWe report a case of a 44-year-old male with a history of asthma who presented with chronic epigastric pain, rectal bleeding, and significant weight loss. Initial investigations, including elevated CRP and fecal calprotectin, suggested inflammatory bowel disease, and treatment was initiated accordingly. However, symptoms persisted, and further evaluations revealed marked eosinophilic infiltration in gastric and colonic biopsies, raising suspicion for eosinophilic gastroenteritis. Repeat endoscopy showed giant gastric folds with significant eosinophilic infiltration (>120 eosinophils/HPF). Imaging demonstrated gastrointestinal wall thickening, biliary involvement, and incidental pulmonary nodules. Bone marrow biopsy revealed preserved trilineage hematopoiesis with prominent eosinophilia. Infectious, autoimmune, allergic, and neoplastic causes were systematically excluded. Cytogenetic testing was negative for PDGFRA, PDGFRB, and FGFR1 mutations, ruling out clonal eosinophilic disorders. Based on persistent peripheral eosinophilia, histologic evidence of tissue infiltration, and exclusion of secondary or clonal causes, a diagnosis of iHES was established in accordance with WHO 2024 criteria. The patient started on systemic corticosteroids, achieving partial symptom relief. Due to relapse during steroid tapering, azathioprine was added as a steroid-sparing agent. Ongoing monitoring was planned with consideration of biologic therapy for future relapses.ConclusionThis case illustrates the diagnostic complexity of iHES presenting with gastrointestinal involvement mimicking inflammatory bowel disease. It highlights the importance of a structured diagnostic approach, including repeated tissue evaluation and hematologic assessment, in differentiating iHES from other eosinophilic and inflammatory disorders.